2005
DOI: 10.1128/aem.71.3.1581-1590.2005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Highly Efficient Sucrose Isomerase from Pantoea dispersa UQ68J and Cloning of the Sucrose Isomerase Gene

Abstract: Sucrose isomerase (SI) genes from Pantoea dispersa UQ68J, Klebsiella planticola UQ14S, and Erwinia rhapontici WAC2928 were cloned and expressed in Escherichia coli. The predicted products of the UQ14S and WAC2928 genes were similar to known SIs. The UQ68J SI differed substantially, and it showed the highest isomaltulose-producing efficiency in E. coli cells. The purified recombinant WAC2928 SI was unstable, whereas purified UQ68J and UQ14S SIs were very stable. UQ68J SI activity was optimal at pH 5 and 30 to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 22 publications
(48 reference statements)
6
93
0
1
Order By: Relevance
“…As glicosiltransferases que convertem a sacarose em isomaltulose descritas na literatura apresentam atividade ótima na faixa de pH 5,0 a 6,5 e temperatura de 30 a 40 ºC e são citadas como sendo termossensíveis [26][27][28][29][46][47][48] . A enzima não purificada de Serratia plymuthica ATCC 15928 foi obtida após centrifugação a 10.000 rpm, por 20 min e rompimento da massa celular em prensa-X 26 .…”
Section: Características Da Glicosiltransferaseunclassified
“…As glicosiltransferases que convertem a sacarose em isomaltulose descritas na literatura apresentam atividade ótima na faixa de pH 5,0 a 6,5 e temperatura de 30 a 40 ºC e são citadas como sendo termossensíveis [26][27][28][29][46][47][48] . A enzima não purificada de Serratia plymuthica ATCC 15928 foi obtida após centrifugação a 10.000 rpm, por 20 min e rompimento da massa celular em prensa-X 26 .…”
Section: Características Da Glicosiltransferaseunclassified
“…Zhang et al (2003a) reported that the reaction end-products were clearly related to the charge of the catalytic pocket. Thus, operating at pHs higher than the enzymes optimal pH allow the formation of trehalulose, whereas at lower pH the production of glucose and fructose was promoted (Nagai et al 1994;Zhang et al 2002;Wu & Birch 2005). The kinetic parameters of various sucrose isomerases are presented in Table 1.…”
Section: Biochemical Properties Of Sucrose Isomerasesmentioning
confidence: 99%
“…LX3 and Enterobacter sp. FMB1 produced essentially isomaltulose with percentages around 75-85% (Cheetham 1984;Veronese & Perlot 1999;Zhang et al 2002;Wu & Birch 2005). Due to difficulties in the chemical synthesis of these sugars, their microbial production is of commercial interest.…”
Section: Properties and Production Of Isomaltulose And Trehalulosementioning
confidence: 99%
“…rhapontici, 12,15) Klebsiella sp. LX3, 40) Klebsiella sp., 41) K. planticola CCRC 19112, 42) Pantoea dispersa, 43) and Enterobacter sp. FMB1, 11) which produce mainly isomaltulose (75 85%), and A. radiobacter MX 332 37) and Ps.…”
Section: )mentioning
confidence: 99%